2021
DOI: 10.1186/s13000-021-01103-5
|View full text |Cite
|
Sign up to set email alerts
|

Optimized workflow for digitalized FISH analysis in pathology

Abstract: Background Effective workflow management in a diagnostic pathology laboratory is critical to achieve rapid turnover while maintaining high quality. Fluorescence in situ hybridization analysis (FISH) is the preferred technique for detecting single chromosomal aberrations in diagnostic surgical pathology. Material and methods FISH analysis applying a rapid hybridization protocol and using an automated whole-slide fluorescence scanning device (3DHISTE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…According to in‐house standard operating procedures, a minimum of four images per FISH analysis were stored allowing retrospective re‐evaluation of the results. Digital pathology measures were not used in this setting as validation of the various FISH probes for sarcomas, including tumour entities with densely packed cells, has proven challenging [ 14 ].…”
Section: Methodsmentioning
confidence: 99%
“…According to in‐house standard operating procedures, a minimum of four images per FISH analysis were stored allowing retrospective re‐evaluation of the results. Digital pathology measures were not used in this setting as validation of the various FISH probes for sarcomas, including tumour entities with densely packed cells, has proven challenging [ 14 ].…”
Section: Methodsmentioning
confidence: 99%
“…Computation cytology bears important role in molecular study. Chea et al 15 showed that WSI of the fluorescent in situ hybridization (FISH) technique scanning had equal performance compared with manual interpretation. The digital slides is of good image quality, and takes significantly less time for analysis.…”
Section: Computational Cytology In the Precise Diagnosis Over The Man...mentioning
confidence: 99%
“…It’s worth highlighting that visualizing in situ hybridization results enables the application of diverse microscopic techniques for 3D signal visualization within tissues ( 35 ). Modern technologies such as FISHQuant, coupled with optimizations in analysis steps utilizing novel buffering systems to enhance tissue sample stability, are gaining widespread adoption ( 36 ).…”
Section: Introductionmentioning
confidence: 99%